Evaluating the impact of pop-off mechanisms in boys with posterior urethral valves - Delefortrie, T.; Ferdynus, C.; Paye-Jaouen, A.; Michel, J. L.; Dobremez, E.; Peycelon, M.; El Ghoneimi, A.; Harper, L. (Frontiers in Pediatrics, 2022)
Introduction Posterior urethral valves are urethral leaflets that cause Lower Urinary Tract Obstruction (LUTO) in boys and are associated with congenital renal dysplasia and abnormal bladder function. They affect 1:4,000 to 1:25,000 births and can be responsible for End-Stage Renal Failure in childhood. There have been several studies on the effect of pop-off mechanisms in boys with posterior urethral valves, but results are contradictory. We aimed to assess and discuss the effect of pop-off mechanisms on renal function in a large cohort of patients. Patients and method Boys with PUV with and without pop-off mechanisms (urinoma, VURD or giant bladder diverticula) were divided into three severity groups for renal function according to their nadir creatinine (low-risk NC < 35 μmol/L, intermediate-risk NC between 35 and 75 μmol/L, and high-risk NC > 75 μmol/L). We compared children with and children without pop-off mechanisms for mean renal function as well as patient distribution within each severity group. Results We included 137 boys of which 39 had a pop-off mechanism. Patients had complete data for at least 5 years follow-up. Though there was no significant statistical difference in mean renal function between the pop-off and non-pop-off group, patient distribution within each severity group varied according to whether patients had a pop-off mechanism or not. Conclusion Though there was no significant difference in mean renal function between boys with and without pop-off mechanisms, it is possible that these are two different patient populations and direct comparison is not possible.